KERANGKA MAQASHID SYARIAH: INTEGRASI EKONOMI SYARIAH DAN PENDIDIKAN AGAMA ISLAM UNTUK MENCEGAH KORUPSI STRUKTURAL - Eny Latifah Latifah; Sitti Atiyatul Mahfudoh; Yusuf Yusuf (Jurnal Multidisipliner Bharasumba, 2026)
This study aims to construct a framework of maqashid al-sharia as the basis for integrating Islamic economics and Islamic religious education to prevent structural corruption in OIC countries. The study employs Systematic Literature Review. Results: The thesis produces five integrations based on the Kulliyat al-Khamsah, namely Hifz al-din (the Islamic Religious Education curriculum incorporates anti-corruption fiqh to legitimize the religious prohibition against bribery), Hifz al-nafs (BMT/pesantren practices cultivate anti-corruption human resources), Hifz al-adl (Sharia audit literacy detects report manipulation), Hifz al-nasl (digital transparency of zakat funds prevents social aid corruption), Hifz al-mal (Sharia governance certification curtails official discretion). Implications: the MEIS-ASC Maqashid-based Islamic Education and Sharia Economy for Anti-Structural Corruption framework as a theoretical innovation. Policies for Indonesia include revising PTKI curricula, “Amanah Officer” certification by OJK-DSN, and involving Islamic boarding schools as KPK partners.